Two-dimensional transition metal carbides and nitrides (MXenes) for biomedical applications. (18th April 2018) - Huang, Kai; Li, Zhongjun; Lin, Jing; Han, Gang; Huang, Peng
Abstract : MXenes with an ultrathin structure and fascinating physiochemical (electronic, optical, magnetic, etc. ) properties have great potential for biomedical applications, such as biosensors, antibacterial materials, bioimaging probes, therapeutics, and theranostics. Abstract : Two-dimensional transition metal carbides and nitrides known as MXenes, with a general formula of M n +1 X n ( n = 1–3), integrate the advantages of metallic conductive transition metals with large groups of carbides, nitrides, or carbonitrides. They have led to a burgeoning research interest in biomedical applications due to their ultrathin structure and fascinating physiochemical (electronic, optical, magnetic, etc. ) properties. In this review, we summarize recent advances in biomedical applications for MXenes. We first introduce the preparation methods and surface modifications with respect to MXenes. Their unique properties are then elaborated. Thirdly, we highlight their various biomedical applications, such as with biosensors, antibacterial materials, bioimaging probes, therapeutics, and theranostics. In the end, the current challenges and new opportunities for MXenes in regard to their biomedical applications are also discussed.